Leveraging the Digital Economy for Tourism Marketing in the Society 5.0 Era: A Case Study of East Kalimantan - Putera, Muhammad Tommy Fimi; Mujanah, Siti; Hwihanus, Hwihanus; Ramadhani, Muhammad Harits Zidni Khatib (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Leveraging digital technology in the Society 5.0 era is crucial for tourism marketing to enhance destination attractiveness. However, prior research has often aggregated various digital platforms. A gap remains in understanding which digital variable—be it social media promotion, platform adoption, or pure technological innovation (e.g., AI/VR)—exerts the most dominant impact on destination attractiveness. This study aims to comparatively analyze the influence of social media utilization, digital platform adoption, and digital technological innovation on tourism attractiveness in East Kalimantan. A quantitative method was employed, utilizing a questionnaire survey administered to 120 respondents (comprising tourists and business stakeholders), with data analyzed via multiple linear regression. The results indicate that while all three variables have a positive and significant influence, digital technological innovation (beta=0.356$) exerts the most dominant effect, surpassing social media utilization (beta=0.324$) and digital platform adoption (beta=0.281$). The model successfully explains 65.9% of the variance in tourism attractiveness. This finding underscores the need for tourism marketing strategies to shift from mere social promotion to the development of robust digital experiences. By implication, stakeholders are urged to prioritize investment in technology-based infrastructure and innovation capacity to navigate competition in the Society 5.0 era.